Optimization of Growth Conditions for Expansion of Cardiac Stem Cells Resident in the Adult Human Heart - kristensson, josefina (My University, 2016)
Cardiovascular diseases such as myocardial infarction and heart failure are major causes of death all around the world. Today there is no way to restore correct function of the heart and the regenerative ability of the heart is limited. However, a number of cardiac stem cell populations have been identified in the adult human heart and can hopefully be utilized for regenerative strategies in the future. One of these populations has been identified based on C-kit+CD45- expression, but this population is committed toward endothelial fate when expanded in vitro. The main goal of the project was to evaluate if different culture conditions can make the cells committed to a cardiac fate instead. The SmartFlare™ technology was evaluated on induced pluripotent stem cells (iPSCs) as a possible method for live cell isolation of stem cell populations in the heart. A method like this is necessary to be able to expand the cells further after isolation, since cardiomyocytes markers are intracellular and sorting with methods such as Fluorescent-Activated Cell Sorting (FACS) requires cell lysis. SmartFlares™ enable live cell detection of gene expression since the probes enter the cells via receptor-mediated endocytosis, interact with the mRNA of interest and thereafter send out detectable fluorescent signals that can be used to isolate cells with FACS technology. An expansion phase of heart biopsy cells in NutriStem followed by the differentiation media DMEM:F12, 10% human serum and dexamethasone (10nM) resulted in most cells committed to cardiac lineage. The method used for evaluation of the different conditions was immunocytochemistry. The SmartFlare™ technology was shown to work well in iPSCs and could be used to detect cardiac troponin I expression in iPSCs differentiated to cardiomyocytes. SmartFlares were also used for sorting out a small population of cardiomyocytes, but analysis using real time quantitative polymerase chain reaction showed that the sorting step needs to be further optimized.
Keywords: Livsvetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Klinisk medicin; Annan medicin och hälsovetenskap; Life Science; Sustainable Development; Innovation & Entrepreneurship; Clinical Medicine; Other Medical Sciences